From carbon to cola: vision of a market for captured carbon dioxide - Chichilnisky, Graciela (Henry Stewart Talks, 2022)
Sustainable development, Carbon negative technology, Global commons, Carbon market, Green Power Fund, Global Thermostat, Carbon dioxide